A SWOT ANALYSIS OF THE STATE AND PRIVATE SCHOOL RATIO IN INDONESIAN EDUCATION POLICY - Maharani, Kiki (STAI Darul Qalam Tangerang, 2025)
This study examines the imbalance between state and private school availability in Indonesia through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis of national education policy. Although the constitution emphasizes the importance of education and the government has allocated significant resources, including the 12-Year Compulsory Education Program and a requirement to dedicate at least 20% of national and regional budgets, the implementation has yet to guarantee fair access to state schools, especially at the secondary level in urban regions. Employing a qualitative-descriptive approach, the analysis is based on primary policy documents, statistical data, and literature reviews. Findings reveal key weaknesses including uneven school distribution, limited capacity, governance gaps, and teacher shortages. Simultaneously, opportunities exist to leverage education funding, zoning policy, decentralization, and digital data systems to address these challenges. However, commercialization trends and rapid urbanization threaten to exacerbate inequality. The SWOT analysis highlights strategic pathways, including state and private partnerships, better spatial planning, and the redistribution of teachers, as means to promote more equitable policy implementation. This study concludes that policy reform must be responsive to spatial and socioeconomic disparities and grounded in cross-sectoral collaboration to realize inclusive and sustainable access to quality public education in Indonesia.